2017
DOI: 10.1253/circj.cj-16-0688
|View full text |Cite
|
Sign up to set email alerts
|

Association of Toll-Like Receptor 4 on Human Monocyte Subsets and Vulnerability Characteristics of Coronary Plaque as Assessed by 64-Slice Multidetector Computed Tomography

Abstract: Background: Although Toll-like receptor 4 (TLR-4) is involved in monocyte activation in patients with accelerated forms of atherosclerosis, the relationship between the expression of TLR-4 on circulating monocytes and coronary plaque vulnerability has not previously been evaluated. We investigated this relationship using 64-slice multidetector computed tomography (MDCT) in patients with stable angina pectoris (SAP). Methods and Results:We enrolled 65 patients with SAP who underwent MDCT. Three monocyte subsets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…For instance, an intervention against glucose fluctuation with acarbose treatment significantly decreased inflammatory cytokines levels followed by reduced serum lipopolysaccharides levels [10]. Considering TLR4, a receptor of lipopolysaccharides, is more expressed on CD14 ++ CD16 + monocytes [38], the link between glucose fluctuation and CD14 ++ CD16 + monocytes is probably existed. Also, a recent ex vitro study showed that hypoglycemia promotes the mobilization of specific leukocyte subsets from the marginal pool and induces proinflammatory functional changes in peripheral blood mononuclear cells [39].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, an intervention against glucose fluctuation with acarbose treatment significantly decreased inflammatory cytokines levels followed by reduced serum lipopolysaccharides levels [10]. Considering TLR4, a receptor of lipopolysaccharides, is more expressed on CD14 ++ CD16 + monocytes [38], the link between glucose fluctuation and CD14 ++ CD16 + monocytes is probably existed. Also, a recent ex vitro study showed that hypoglycemia promotes the mobilization of specific leukocyte subsets from the marginal pool and induces proinflammatory functional changes in peripheral blood mononuclear cells [39].…”
Section: Discussionmentioning
confidence: 99%
“…However, classical monocyte counts could not be associated with plaque stability or increased chance of cardiac events after carotid endarterectomy in patients with already existing atherosclerotic plaques (94). Additionally, other studies demonstrated that elevated intermediate monocyte counts play a pivotal role in the growth and stability of already existing atherosclerotic plaques or cardiac attacks (8688, 97, 98). Elevated CCL2 levels in the early phases of the development of atherosclerotic plaques may lead to increased classical monocyte counts and could thus be considered a predictive marker, while later on, the presence of necrotic cores may rather recruit non-classical monocytes to control vascular homeostasis and the clearance of debris (21, 99, 100).…”
Section: Monocytes and Monocyte-derived Cells In Atherosclerosismentioning
confidence: 99%
“…Indeed, HDLs were recently shown to exert a proinflammatory effect on mouse and human macrophages, possibly due to lipid raft disruption secondary to cholesterol depletion and subsequent activation of TLRs and protein kinase C signaling [19, 20]. Circulating monocytes of subjects with vulnerable atherosclerotic plaques in the coronary arteries express higher levels of TLR-4 when compared to subjects with stable coronary artery atherosclerosis [21]. Similarly, subjects with unstable angina had higher levels of expression of TLR-4 on circulating monocytes when compared to asymptomatic subjects with cardiovascular risk factors [22].…”
Section: Macrophages Initiate Local Inflammation In Nascent Atheromentioning
confidence: 99%
“…In addition, patients with a thin cap fibroatheroma were shown to have the largest number of circulating CD14 hi CD16 + monocytes [67]. In a recent study by Ozaki et al on 65 subjects undergoing coronary multidetector computed tomography, the proportion of circulating CD14 hi CD16 + monocytes expressing TLR-4 was shown to be higher in subjects with plaque features of vulnerability [21]. However, a prospective study involving 191 subjects with chronic kidney disease was unable to demonstrate any association between the number of CD14 + TLR-4 + monocytes and incident cardiovascular events [68].…”
Section: Circulating Monocyte Subsets In Human Atherosclerosismentioning
confidence: 99%